1997
DOI: 10.1164/ajrccm.155.5.9154870
|View full text |Cite
|
Sign up to set email alerts
|

L-canavanine improves organ function and tissue adenosine triphosphate levels in rodent endotoxemia.

Abstract: Overproduction of NO by an inducible NO synthase (iNOS) plays a major role in the pathophysiology of septic shock, and selective inhibition of iNOS in this setting could be of great therapeutic value. In the present study, we evaluated the effects of L-canavanine, a selective iNOS inhibitor, in an animal model of septic shock, with a particular focus on tissue oxidative metabolism and organ functions. Anesthetized rats challenged intravenously with lipopolysacharide (LPS) were treated after 1 h by a continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 33 publications
2
19
0
1
Order By: Relevance
“…Patil et al (40) recently demonstrated reduced renal electron transport chain complex I and complex II/III activity occurring as early as 6 h after cecal ligation and puncture in mice. Furthermore, a reduction of renal ATP levels has been observed in rodent models of sepsis-induced AKI which correlated well with renal dysfunction (32,40,49). Taken together, these data provide strong evidence that mitochondrial dysfunction plays a central role in the pathophysiology of sepsis-induced AKI.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patil et al (40) recently demonstrated reduced renal electron transport chain complex I and complex II/III activity occurring as early as 6 h after cecal ligation and puncture in mice. Furthermore, a reduction of renal ATP levels has been observed in rodent models of sepsis-induced AKI which correlated well with renal dysfunction (32,40,49). Taken together, these data provide strong evidence that mitochondrial dysfunction plays a central role in the pathophysiology of sepsis-induced AKI.…”
Section: Discussionmentioning
confidence: 97%
“…Suppression of mitochondrial mRNAs correlated with renal function as measured by blood urea nitrogen (BUN) (62). LPS-induced mitochondrial dysfunction results in a decline (ϳ50%) in renal ATP content within 5 h of exposure in rodents, likely contributing to changes in renal function in this model of septic AKI (32). Disruption of renal mitochondrial function and ATP production has also been reported in the cecal ligation and puncture model (CLP) of sepsis (40).…”
mentioning
confidence: 92%
“…A group of five mice not receiving LPS or flagellin was used for control purposes. The dose of LPS administered in this study was selected on the basis of numerous previous works evaluating the effects of LPS in rodents, where doses in the milligram-per-kilogram range were generally administered (9,17,31,33). Accordingly, we used a similar dose of flagellin.…”
Section: Methodsmentioning
confidence: 99%
“…The latter is an index of whole-body production of nitric oxide. Nitrate was determined by a spectrophotometric assay based on the oxidation of NADPH during the enzymatic conversion of nitrate to nitrite by a nitrate reducatase, as previously described [24].…”
Section: Protocolmentioning
confidence: 99%